The Mediating Effect of Efficiency on the Impact of Managerial Ownership on Firm Value Moderated by Firm Size and Risk Using Macro PROCESS - Aldi Akbar; Nugraha Nugraha; Disman Disman; Ikaputera Waspada (International Journal of Artificial Intelligence Research, 2024)
The phenomenon of firm value is still an interesting topic to research in the field of financial management, especially those caused by managerial ownership. Not all studies explore the efficiency mechanism and test it up to the boundary conditions of the effect itself. This study uses firm size and risk as factors to explain how efficiency mediates the impact of managerial ownership on firm value both directly and indirectly. The sample used in this study is the financial statements of companies listed on the Indonesia Stock Exchange with a period range of financial statements from 2010 to 2019. This study uses Conditional Process Analysis techniques with implementing of macro PROCESS embedded on SPSS version 21 software to find out how the mechanism (efficiency) varies as a function of individual differences (company size and risk). The results obtained are, large companies in Indonesia tend to have been managed efficiently so that they are able to deal with various levels of risk while small and medium-sized companies provide the opposite results. Firm size and stock return risk determine the indirect impact of efficiency on the effect of managerial ownership on firm value. Another finding is that the measurement of the direct impact of managerial ownership on firm value is not moderated by firm size and also the level of risk. Firm size (small, medium, large) and stock return risk (low, moderate, high) both have no contributory effect on the direct effect of managerial ownership on firm value